Different Accumulation of Elements in Proximal and Distal Parts of the Left Anterior Descending Artery Beneath the Myocardial Bridge - Yoshiyuki Tohno (2018)
© 2015, Springer Science+Business Media New York. To elucidate the action of the myocardial bridge (MB) on the coronary artery, the authors first prepared the hearts with the MB located in the middle one third of the left anterior descending (LAD) artery and then investigated element accumulation in the LAD artery of the hearts with the MB by direct chemical analysis. Eighty-four formalin-fixed adult Thai hearts were dissected and the MBs were found in 39 of 84 hearts with a total of 44 MBs. The 37 MBs were located in the middle one third of the LAD artery. To examine the action of the MB on element accumulation in the LAD artery, the hearts with the MB which was located in the middle one third of the LAD artery and was longer than 1.5 cm were used as Materials. The left main coronary (LMC) and LAD arteries were removed from these hearts successively and the isolated arteries were divided into eight to ten segments. After incineration of arteries with nitric acid and perchloric acid, seven element contents of Ca, P, S, Mg, Zn, Fe, and Na were determined by inductively coupled plasma-atomic emission spectrometry. To examine the endothelial changes of the LAD artery, the inner surface of segments of the LAD artery was observed by scanning electron microscopy. It was found that the extent of accumulation of Ca, P, Zn, and Na was not uniform throughout the LAD artery and was higher in the proximal part than in the distal part with regard to the LAD artery beneath the MB (the tunneled LAD artery). The extent of accumulation of Ca, P, Zn, and Na in the proximal part of the tunneled LAD artery was similar to that in the segments proximal to the MB, whereas the extent of accumulation of Ca, P, Zn, and Na in the distal part of the tunneled LAD artery was similar to that in the segments distal to the MB.